2018
DOI: 10.1186/s12889-018-5151-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of working beyond retirement in older workers with and without a chronic disease - results from data linkage of Dutch questionnaire and registry data

Abstract: BackgroundAn increasing number of retirees continue to work beyond retirement despite being eligible to retire. As the prevalence of chronic disease increases with age, working beyond retirement may go along with having a chronic disease. Working beyond retirement may be different for retirees with and without chronic disease. We aim to investigate whether demographic, socioeconomic and work characteristics, health and social factors predict working beyond retirement, in workers with and without a chronic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 17 publications
3
28
0
1
Order By: Relevance
“…As expected, good-physical-health enabled older workers to work beyond the statutory retirement age. This finding supports previous research showing that good health—both physically and mentally—(Demou et al 2017 ) and the absence of a chronic disease (De Wind et al 2018 ) are associated with working beyond retirement. A good health condition is also an important factor in the decision-making process to retire or work beyond the retirement age (Dingemans et al 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, good-physical-health enabled older workers to work beyond the statutory retirement age. This finding supports previous research showing that good health—both physically and mentally—(Demou et al 2017 ) and the absence of a chronic disease (De Wind et al 2018 ) are associated with working beyond retirement. A good health condition is also an important factor in the decision-making process to retire or work beyond the retirement age (Dingemans et al 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…For example, recent insights suggested that good health—both physically and mentally—along with a need or desire to stay in employment are important reasons to work beyond the statutory retirement age (Demou et al 2017 ). This was also seen in a study by de Wind et al ( 2018 ) who found that workers without a chronic disease were more likely to work past the statutory retirement age compared to those with a chronic disease. Additionally, bridge employment offers the opportunity to engage in physical, cognitive and social activities which could lead to a higher quality of life.…”
Section: Introductionsupporting
confidence: 69%
“…Due to the signi cant impact of health on employment, there are major health disparities between those who work or can work and those who cannot. For example, 27% of people without chronic disease are more likely to work beyond the recommended retirement age compared to 23% people with a chronic disease [21]. A diagnosis of diabetes is associated with a 30% increase in the rate of labour-force exit in Europe and the US [26].…”
Section: Previous Researchmentioning
confidence: 99%
“…Further, job loss or unemployment is associated with an increased risk in morality and cardiac events [22]. Among older workers those remaining in employment for longer are healthier than their unemployed or involuntarily retired counterparts [4,21]. Along with diverging health outcomes, a similar widening is occurring in economic resources in the older population [20,26].…”
Section: Previous Researchmentioning
confidence: 99%
“…poprzez interwencję chirurgiczną, może sprzyjać powrotowi do aktywności zawodowej) [37]. Ponadto brak chorób przewlekłych wiąże się z częstszym kontynuowaniem pracy na emeryturze [38].…”
Section: Wpływ Zdrowia Personelu Na Kurczenie Się Zasobów Pracyunclassified